TINJAUAN KAWIN HAMIL DALAM PERSPEKTIF HUKUM ISLAM - Fauzi, Fahrul (Journal of Islamic Law Studies, 2021)
Marriage is a spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the Godhead of the Almighty. Basically, in the opinion of some scholars from the origin of the law of marriage if connected with al-ahkam al-khamsah is permissibility or ibahah. But marriage as a condition to meet the needs of physical life (biological needs) is often bypassed. The fact that there is currently increasingly widespread premarital sex. One of the effects of premarital sex is pregnant out of wedlock. The practice in Indonesia when the woman is pregnant it will soon be married. Pregnant marriage is marriage to a woman who is pregnant out of wedlock, both married by the man who impregnated her and by a man who did not impregnate her. There are several differences of opinion between the four Imams Mazhab: Imam Syafi'i, Imam Abu Hanifa, Imam Malik bin Anas, Imam Hanbali, and several other imams. The Compilation of Islamic Law (KHI) also regulates marriages with pregnant women. This paper will further discuss the differences of opinion regarding pregnant marriage in the perspective of Islamic law.